MITIGATING CROSS-BORDER CONFLICTS BETWEEN ETHIOPIA AND SOUTH SUDAN - Pandey, Deep Narayan; Choubey, Awadh Narayan; Saini, Satish Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The Ethiopia-South Sudan border, particularly in Gambella Regional State, epitomizes the multifaceted insecurity in the Horn of Africa. The region is marked by a lack of development, political marginalization, and limited access to essential public services, making its residents extremely vulnerable to various forms of insecurity. The porous nature of the border exacerbates these challenges, as the free movement of people and goods facilitates not only illicit trade, but also violent activities such as child abduction, cattle rustling, and arms smuggling. These cross-border conflicts are further fueled by the instability in South Sudan, as well as challenges to economic inclusion and governance on both sides of the border. As a result, Governments should enhance cross-border security operations, targeting insurgent groups and smuggling networks. Improved communication and joint patrols between Ethiopian and South Sudanese security forces can help curtail illicit activities.